Interface-driven spin pumping and inverse Rashba-Edelstein effect in FeGaB/Ag/BiSb multilayers - Vinay Sharma; Prabesh Bajracharya; Anthony Johnson; Ramesh C. Budhani (AIP Advances, 2022)
Spin-orbit-coupling (SOC) plays a critical role in spin-to-charge conversion (SCC) mechanism. The SCC process is usually investigated by injecting a spin current from ferromagnet (FM) into a large SOC normal metal (SOC-NM) and then measuring the voltage generated by inverse spin Hall effect (ISHE). Recently, a new mechanism of SCC at inversion symmetry breaking interfaces between topological insulators (TIs) and magnetically ordered materials has been introduced, which is driven by the inverse Rashba-Edelstein effect (IREE). Motivated by this result, we have investigated the IREE effect of a simple binary three-dimensional TI Bi85Sb15 (BiSb). The model system used here is a trilayer of FeGaB/Ag/BiSb with different Ag thickness made insitu with a combination of dc magnetron sputtering and pulsed laser ablation. The SCC efficiency has been evaluated by measuring ferromagnetic resonance (FMR) driven ISHE voltage and extraction of the Gilbert damping (α) and interfacial spin mixing conductance (g↑↓) from the FMR line shape analysis. It is interesting to note that the charge current (Ic) increases with Ag thickness. This observation indicated that the IREE process at the Ag/BiSb interface dominates over ISHE in the bulk of BiSb film. The conversion efficiency of IREE is determined by calculating the IREE length (λIREE), which increases with the thickness of the Ag layer. These findings offer a method to generate and detect the IREE in a room temperature deposited heterostructure using simple coplanar waveguide setup.